2015
DOI: 10.3171/2014.12.peds13675
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in CSF shunt infection over a 10-year period associated with the application of concentrated topical antibiotic powder directly to surgical wounds prior to closure

Abstract: OBJECT The application of concentrated topical antibiotic powder directly to surgical wounds has been associated with a reduction in wound infection in cardiac, spinal, and deep brain stimulator surgery. As a result of these findings, the corresponding author began systematically applying concentrated bacitracin powder directly to wounds during shunt surgery more than 5 years ago. The object of this study was to evaluate the effectiveness of concentrated bacitracin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Our retrospective analysis of shunt infection over 10 years, divided between periods when bacitracin was and was not used, suggested that a reduction in shunt infection was at least partially associated with the use of bacitracin powder. 4 However, given the limitations of a retrospective study, prospective controlled trials are required before this practice can be broadly recommended. We conducted the analysis in this report to further study the possible complications associated with applying high-dose bacitracin directly to surgical wounds prior to closure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our retrospective analysis of shunt infection over 10 years, divided between periods when bacitracin was and was not used, suggested that a reduction in shunt infection was at least partially associated with the use of bacitracin powder. 4 However, given the limitations of a retrospective study, prospective controlled trials are required before this practice can be broadly recommended. We conducted the analysis in this report to further study the possible complications associated with applying high-dose bacitracin directly to surgical wounds prior to closure.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we reanalyzed the same patient cohort previously used to study the effect of bacitracin powder on CSF shunt infection rates in children over a 10-year period. 4 Of the 658 patients who underwent surgery by the corresponding author (G.F.T.) at All Children's Hospital during that time period, we previously reported on 539 patients who had at least 180 days of follow-up, to assess shunt infection.…”
Section: Methods Study Populationmentioning
confidence: 99%
See 3 more Smart Citations